Randomised clinical trial of early specialist palliative care plus standard care versus standard care alone in patients with advanced cancer: The Danish Palliative Care Trial. (October 2017) - Groenvold, Mogens; Petersen, Morten Aagaard; Damkier, Anette; Neergaard, Mette Asbjoern; Nielsen, Jan Bjoern; Pedersen, Lise; Sjøgren, Per; Strömgren, Annette Sand; Vejlgaard, Tove Bahn; Gluud, Christian; Lindschou, Jane; Fayers, Peter; et al.
Background: Beneficial effects of early palliative care have been found in advanced cancer, but the evidence is not unequivocal. Aim: To investigate the effect of early specialist palliative care among advanced cancer patients identified in oncology departments. Setting/participants: The Danish Palliative Care Trial (DanPaCT) (ClinicalTrials.gov NCT01348048) is a multicentre randomised clinical trial comparing early referral to a specialist palliative care team plus standard care versus standard care alone. The planned sample size was 300. At five oncology departments, consecutive patients with advanced cancer were screened for palliative needs. Patients with scores exceeding a predefined threshold for problems with physical, emotional or role function, or nausea/vomiting, pain, dyspnoea or lack of appetite according to the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) were eligible. The primary outcome was the change in each patient's primary need (the most severe of the seven QLQ-C30 scales) at 3- and 8-week follow-up (0–100 scale). Five sensitivity analyses were conducted. Secondary outcomes were change in the seven QLQ-C30 scales and survival. Results: Totally 145 patients were randomised to early specialist palliative care versus 152 to standard care. Early specialist palliative care showed no effect on the primary outcome of change in primary need (−4.9 points (95% confidence interval −11.3 to +1.5 points); p = 0.14). The sensitivity analyses showed similar results. Analyses of the secondary outcomes, including survival, also showed no differences, maybe with the exception of nausea/vomiting where early specialist palliative care might have had a beneficial effect. Conclusion: We did not observe beneficial or harmful effects of early specialist palliative care, but important beneficial effects cannot be excluded.